Isoaspartate Accumulation in Mouse Brain Is Associated with Altered Patterns of Protein Phosphorylation and Acetylation, Some of Which Are Highly Sex-Dependent - Qin, Zhenxia; Kaufman, Rachel S.; Khoury, Rana N.; Khoury, Mitri K.; Aswad, Dana W. (PLOS ONE, 2013)
Isoaspartate (isoAsp) formation is a major source of protein damage that is kept in check by the repair function of protein L-isoaspartyl methyltransferase (PIMT). Mice deficient in PIMT accumulate isoAsp-containing proteins, resulting in cognitive deficits, abnormal neuronal physiology and cytoarchitecture, and fatal epileptic seizures 30–60 days after birth. Synapsins I and II, dynamin-1, collapsin response mediator protein 2 (CRMP2), and α/β-tubulin are major targets of PIMT in brain. To investigate links between isoAsp accumulation and the neurological phenotype of the KO mice, we used Western blotting to compare patterns of in vivo phosphorylation or acetylation of the major PIMT targets listed above. Phosphorylations of synapsins I and II at Ser-9 were increased in female KO vs. WT mice, and acetylation of tubulin at Lys-40 was decreased in male KO vs. WT mice. Average levels of dynamin-1 phosphorylation at Ser-778 and Ser-795 were higher in male KO vs. WT mice, but the statistical significance (P>0.1) was low. No changes in phosphorylation were found in synapsins I and II at Ser-603, in CRMP2 at Ser-522 or Thr-514, in DARPP-32 at Thr-34, or in PDK1 at Ser-241. General levels of phosphorylation assessed with Pro-Q Diamond stain, or an anti-phosphotyrosine antibody, appeared similar in the WT and KO mice. We conclude that isoAsp accumulation is associated with altered functional status of several neuronal proteins that are highly susceptible to this type of damage. We also uncovered unexpected differences in how male and female mice respond to isoAsp accumulation in the brain.